Cover Picture: Controlling Porosity in Lignin‐Derived Nanoporous Carbon for Supercapacitor Applications (ChemSusChem 3/2015). Issue 3 (23rd January 2015) - Jeon, Ju‐Won; Zhang, Libing; Lutkenhaus, Jodie L.; Laskar, Dhrubojyoti D.; Lemmon, John P.; Choi, Daiwon; Nandasiri, Manjula I.; Hashmi, Ali; Xu, Jie; Motkuri, Radha K.; Fernandez, Carlos A.; Liu, Jian; et al.
<x xml:space="preserve">Abstract</x> The Front Cover image illustrates various pathways to achieve renewable energy storage. Low‐cost renewable lignin has been used as a precursor to produce high‐surface, graphitized porous carbons. These carbonized residues exhibit relatively high electrochemical performance in terms of specific capacitance, energy density, and power with good capacity retention. More details can be found in the Full Paper by Jeon et al. on page 428 (DOI: 10.1002/cssc.201402621).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>